Visitor Motivation, Experience, and Visit Intention: Music Festivals in Bandung City - Saputra, Adnan Zaidan Eka; Kusumah, Ahmad Hudaiby Galih (E-Journal of Tourism; Volume 11 Number 2 (September 2024)DO - 10.24922/eot.v11i2.121442, 2024)
This paper discusses the motivations of visitors to music festivals in Bandung. The majority of respondents gave a positive rating to 'enjoying the atmosphere of the music festival,' indicating that festivals are a means of unwinding and creating tranquillity. Motivations were split between explicit and implicit experiences, and influenced by satisfaction with the culinary aspects of the festival. In the context of return visits, positive experiences, 'interest,' and satisfaction with performance were the main factors influencing visitors' decision to return. Previous experiences at music festivals form trust and influence interest in visiting other music festivals. The analysis shows that visit motivation is influenced by experience, satisfaction with performance, and music festival atmosphere. The 'interest' factor also has a significant impact. The complex interactions between experience, performance, and atmosphere create a strong motivational foundation for visitor participation in music festivals.